2021
DOI: 10.1001/jamasurg.2021.2866
|View full text |Cite
|
Sign up to set email alerts
|

Association of Enhanced Recovery Pathway Compliance With Patient Outcomes

Abstract: Enhanced recovery pathways (ERPs) have emerged as one of the most effective strategies to improve clinical outcomes and reduce health care utilization in elective colorectal surgery. However, ERP implementation alone does not result in improvement without high pathway component compliance. 1,2 Hospital collaboratives have been used to accelerate quality improvement across clinical areas, including ERP adoption. [3][4][5] Despite collaborative participation, hospitals are frequently hindered by barriers relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…These changes, especially related to the substantially reduced hospitalization durations, disrupt standard care plans and generate new patient care demands. In addition, most existing ERAS programs are based on expert consensus and lack consideration of the patient perspective, undermining patient compliance rates and intervention effects (Fischer et al, 2021; Forsmo et al, 2016). The care requirements of patients under the new ERAS paradigm have yet to be extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…These changes, especially related to the substantially reduced hospitalization durations, disrupt standard care plans and generate new patient care demands. In addition, most existing ERAS programs are based on expert consensus and lack consideration of the patient perspective, undermining patient compliance rates and intervention effects (Fischer et al, 2021; Forsmo et al, 2016). The care requirements of patients under the new ERAS paradigm have yet to be extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…3,5,6 Not surprisingly, the advent of more multifaceted and thus complicated ERAS programs and protocols have often hampered their success. 3,6,7 There is an increasing opportunity and impetus for ambulatory surgery with extended recovery, in which patients are admitted, operated on, and stay for 1 night postoperatively, with an overall stay up to 23 hours. 6 It has been reported that total knee arthroplasty can be performed safely as an outpatient procedure in a subset of healthy patients 65 years or older, with a complication rate similar to an inpatient stay.…”
mentioning
confidence: 99%
“…3,5,6 Not surprisingly, the advent of more multifaceted and thus complicated ERAS programs and protocols have often hampered their success. 3,6,7…”
mentioning
confidence: 99%
See 1 more Smart Citation